FORMULASI SANKSI TINDAKAN TERHADAP PELAKU SODOMI SEBAGAI SANKSI TAMBAHAN DALAM PEMBAHARUAN HUKUM PIDANA INDONESIA - Feriska Bulan Mutia; Ferawati Ferawati; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The rise of sodomy crimes in Indonesia is very worrying, especially sodomy crimesagainst children (homosexuals). One of the reasons for this rise is the lack of effectiveness inlaw enforcement against sodomy perpetrators, of course, in a preventive or curative way. TheIndonesian Criminal Law already regulates the imposition of sanctions against perpetratorsof sexual crimes against children. However, this has not been able to have a significantimpact on reducing sodomy cases. For this reason, more effective forms of prevention areneeded. The purpose of writing this thesis: First, to find out the urgency of imposingsanctions against sodomy perpetrators in the renewal of Indonesian criminal law. Second, toformulate sanctions against sodomy perpetrators as additional sanctions in the renewal ofIndonesian criminal law.The type of research used in this legal research is normative legal research.The approach used by researchers is a normative juridical approach. Data analysis used byresearchers is to analyze data qualitatively. In drawing conclusions the researcher uses thedeductive thinking method, namely a way of thinking that draws conclusions from a statementthat is general in nature to a statement that is specific in nature.From the results of the study, it is important to apply sanctions against sodomyperpetrators against children to provide prevention efforts to reduce sodomy crimes. With therenewal of the criminal law, it is hoped that it will provide clear regulations in the future,especially regarding sodomy crimes against children. A formulation in the application ofsanctions against sodomy perpetrators, by imposing sanctions on sodomy offenders againstchildren, is an effective step in tackling sodomy crimes against children.Keywords: Sanction Formulation, Additional Penalty, Action, Sodomy, Criminal LawReform